Effects of three pre-treatment techniques on dormancy and germination of seeds of Afzelia africana (Sm. Ex pers) - Amusa (Global Journal of Food and Agribusiness Management, 2019)
The study assessed the effects of three pre-treatment techniques on dormancy and germination of seeds of Afzelia africana (Sm. ex Pers), an endangered tree species in Savanna ecozone of Nigeria. The three pretreatment techniques are: soaking in cold water for 1, 12 and 24 h, soaking in hot water (100◦C) for 1, 12 and 24 h and soaking in 10, 50 and 98% concentrated sulphuric acid (H2SO4) for 5, 10 and 30 min. Experiments were performed based on a completely randomized design with four replicate. The results show that cold water pre-treatment of A. africana seeds only gave a fair germination percentage (33.33 to 53.33%) and reduced dormancy period. On the other hand, the effect of hot water pre-treatment on the seeds gave adverse result (26.67 to 36.67%). Although A. africana seeds under control treatment gave an impressive germination, which did not differ significantly from the results of other pre-treatment techniques (F-cal = 2.6777; P-level = 0.1180; P < 0.05), acid pre-treatments yield a more uniform and regular germination. Thus, while the seeds of A, africana could be germinated without pre-treatment, to attain higher percentage germination and reduced dormancy period, the seeds should be pre-treated with sulphuric acid.